Professional development research on promoting productive practices for teachers’ handling of typical tasks of mathematics teaching: a systematic review - Shure, Victoria; Lehmann, Malte; Friesen, Marita; Rösken-Winter, Bettina; Prediger, Susanne (ZDM, 2025)
While existing surveys on professional development (PD) programs for mathematics teachers revealed a substantial growth in PD research studies, there has been a call for more in-depth reports. Inspired by reviews on practice-based pre-service teacher education, this systematic review focuses on PD activities developed and investigated for enhancing teachers’ practices for handling relevant tasks of mathematical teaching, to provide an overview of the state of PD research for practicing teachers. To accomplish this, keywords were used to identify relevant research, complemented by hand-searched papers which are in the core of the topic yet do not use the keywords. Based on the full-text analysis of 32 peer-reviewed studies, this systematic review uncovered the emphasis of the most studies on the task of supporting and enhancing student learning followed by noticing and assessing student thinking, with variation in associated teaching practices. Differences in the level of reporting on PD activities were revealed concerning both the PD design and the research about PD. Tendencies in the types of frameworks for designing PD were also found, with almost half the studies situating teacher learning in practice. Overall, this review not only advances the field by making findings on teacher practices to handle tasks of teaching more comparable, but by gaining insights into the types of corresponding PD activities.
Gesehen am 30.07.2025